Questioning the stereotype of the "malingering bureaucrat" absence from work in the public and private sector in Germany - Stephanie Prümer; Claus Schnabel (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2019)
Public sector employees are often said to have excessive rates of absence from work. Using representative survey data for Germany, we indeed find absenteeism of employees to be higher in the public than the private sector. The differences in the incidence and days of absence showing up in descriptive statistics are substantially reduced and partly disappear in our estimates of hurdle regression models controlling for individuals' socio-demographic characteristics, health status, professional activities, and for many workplace-related factors. Nevertheless, the probability of staying home sick at least once a year is still 5.6 percentage points higher in the public sector, ceteris paribus. This finding refutes popular assertions that differences in absence rates between the sectors are mainly due to structural factors like different compositions of the workforce. We show that the same observable factors play a role for absenteeism in the public and private sector, but we cannot rule out that shirking may play a more important role in the public sector. Nevertheless, we conclude that the stereotype of the "malingering bureaucrat" seems to be an exaggeration, at least for Germany. – – Von Beschäftigten im Öffentlichen Sektor wird oft behauptet, dass sie sich übermäßig häufig bzw. lange krankmelden. Mithilfe von repräsentativen Befragungsdaten für Deutschland finden wir tatsächlich höhere Fehlzeiten im Öffentlichen Sektor als im Privaten Sektor. Die Unterschiede im Auftreten von Fehlzeiten und in der Zahl der Fehltage aus rein deskriptiven Auswertungen werden wesentlich reduziert und verschwinden teilweise sogar, wenn in Regressionsmodellen für soziodemografische Merkmale und den Gesundheitsstatus der Beschäftigten, Berufsfelder sowie eine Vielzahl von Arbeitsplatzcharakteristika kontrolliert wird. Dennoch ist die Wahrscheinlichkeit, sich im vergangenen Jahr mindestens einmal krankgemeldet zu haben, im Öffentlichen Sektor ceteris paribus immer noch 5,6 Prozentpunkte höher als im Privaten Sektor. Dies widerspricht der Behauptung, dass Unterschiede in den Fehlzeiten zwischen den beiden Sektoren lediglich auf strukturelle Faktoren wie die Zusammensetzung der Belegschaft zurückzuführen sind. Wir zeigen, dass die gleichen beobachtbaren Faktoren für Fehlzeiten im Öffentlichen und Privaten Sektor von Bedeutung sind. Dabei können wir nicht ausschließen, dass "Blaumachen" im Öffentlichen Sektor eine größere Rolle spielt. Dennoch scheint das Vorurteil exzessiver Fehlzeiten im Öffentlichen Sektor zumindest für Deutschland übertrieben zu sein.
Keywords: I19; J22; H8; 330; absenteeism; public sector; sick leave; Germany